Kurtun Dam oscillate characterization with landslide possible effect detection using InSAR observations - Celik, Fatih; Sanli, Fusun Balik; Celik, Kemal; Celik, Ayse (SPRINGER, 2025)
Observing and analyzing areas prone to landslides is crucial due to the extensive destructive capacity of landslides. To monitor landslide activities across diverse areas, remote sensing data and image processing methods are employed. This study proposes a method that integrates Multi-temporal Interferometric Synthetic Aperture Radar and advanced temporal tracking technologies to intensify surveillance of the Kurtun Dam and its valley. According to Sentinel-1 A data, the net displacement rates of the dam crest varied between - 12 and 2 mm/year (LOS). InSAR technology surveys the entire dam catchment area, detecting critical infrastructure such as slopes, spillways, and access roads. The crest of the Kurtun Dam experiences oscillatory deformation during filling activities, but the lateral slopes and downstream abutment remain stable. As reservoir water levels rise, the dam structure exhibits downstream deformations, whereas declining water level results in upstream displacements. Monitoring points located the opposite Ozkurtun settlement and within the reservoir area, both facing the dam, exhibited displacement rates of up to -50 mm monthly. In regions susceptible to landslides, the greatest annual displacement rates were observed to be -54 and - 127 mm/year. This study suggests that integrating 3D modeling with InSAR technology into dam monitoring systems can significantly enhance their effectiveness. At Kurtun Dam and other crucial locations within the catchment area, the integrated approach combined with topographic monitoring, ensures reliable landslide detection and analysis. By advancing monitoring technology for embankment dams, this strategy prioritizes safety and structural integrity assessments.
Keywords: Landslide detection; Dam monitoring; Multi-temporal SAR; InSAR; Time series; ATATURK DAM; DEFORMATION; RESERVOIR; Geology; Meteorology & Atmospheric Sciences; Water Resources